Research Progress of Gallium Nitride Microdisk Cavity Laser - Zhu, Gangyi; Qin, Feifei; Li, Xin; Sun, Yang; Gao, Fei; Tian, Mufei; Ji, Baojian; Wang, Yongjin (Frontiers in Materials, 2022)
Whispering gallery mode (WGM) cavities provide resonance configurations for light propagation through internal reflection, achieving high Q factors, low thresholds, and small mode volumes. GaN-Based materials exhibit high freedom in band engineering and are highly compatible with contemporary semiconductor processing technology. Recently, Lasers from artificial GaN microdisks, obtained by combining the excellent material properties of GaN with the advantages of WGM, have attracted considerable research attention. These have wide application scope in optical communication, display, and optoelectronic integration. In this review, we summarize the recent advances in GaN-based WGM microlasers, including the fabrication methods for GaN microcavities, observations of optical pumped GaN microdisk lasing, lasing mechanisms, comparison of Q factors, lasing modes and threshold properties, commonly used light field control techniques, and mode clipping methods. Further, we introduce the recent advances in electrically driven GaN-based laser diodes, followed by research challenges and strategies for promising applications, such as electrically pumped lasers and optoelectronic chip integration.